2015
DOI: 10.4049/jimmunol.1401533
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the HCK and FGR src-Family Kinases in FCRL4-Mediated Immune Regulation

Abstract: FCRL4 is an immunoregulatory receptor expressed by a subpopulation of memory B cells. These tissue-based cells express increased levels of the src-family kinases HCK and FGR. In this study, we investigate the roles of these src-family kinases in FCRL4-mediated immunoregulation of B cells in the context of previously unrecognized palmitoylation of the receptor. We observed enhanced phosphorylation of FCRL4 on tyrosine residues in the presence of the HCK p59 or FGR. This phosphorylation was markedly reduced in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
(65 reference statements)
1
19
0
Order By: Relevance
“…Further, HcK downmodulation resulted in a reduction of TLR-signaling in FcRL4 B-cell transfectants. These data confirm recent reports by Liu et al ( 33 ) and suggest that FcRL4 in human B cells likely recruits the Src-kinase family member HcK, resulting in amplification of TLR-signaling. However, further studies are needed to determine the precise association between FcRL4 and HcK.…”
Section: Discussionsupporting
confidence: 92%
“…Further, HcK downmodulation resulted in a reduction of TLR-signaling in FcRL4 B-cell transfectants. These data confirm recent reports by Liu et al ( 33 ) and suggest that FcRL4 in human B cells likely recruits the Src-kinase family member HcK, resulting in amplification of TLR-signaling. However, further studies are needed to determine the precise association between FcRL4 and HcK.…”
Section: Discussionsupporting
confidence: 92%
“…The equine T-bet + B cell populations identified in the present study share many features with the atypical memory B cell populations described in humans. In addition to TBX21/T-bet expression, horse T-bet + B cell populations exhibit similar gene expression patterns, including enriched expression of FCRL4, FGR, and HCK, the protein products of which modulate BCR signaling (38). Furthermore, a recent study of T-bet + B cells in HIV demonstrated that they express genes characteristic of germinal center B cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, T-bet + B cells have been described as "atypical memory B cells," appearing in the peripheral blood during chronic infection and/or inflammation (17,34). Although specific markers and/or gene expression patterns vary in different datasets, these B cells are often found to express ITGAM (CD11b), ITGAX (CD11c), as well as genes that modulate BCR signaling (including FCRL4, FGR, and HCK) (35)(36)(37)(38)(39). Moreover, a recent study of T-bet + B cell populations in the context of chronic HIV infection demonstrated expression of genes associated with germinal center B cells (16,40).…”
Section: Equine T-bet + B Cells Share Gene Expression Features With Hmentioning
confidence: 99%
“…Molecular dissection of the FCRL4 cytoplasmic tail has demonstrated that its function is altered by the recruitment of at least two different SFKs. FCRL4 wields suppressive activity in B cells co-expressing FGR, but promotes activation in B cells co-expressing HCK p59 ( 26 ). Thus, as opposed to the classical FCR for IgG and IgE, these findings highlight that many FCRLs possess multifaceted regulatory potential.…”
Section: Fc Receptor-like Molecules (Fcrl) In B Cell Regulationmentioning
confidence: 99%